As clear as glass: How figurativeness and familiarity impact simile processing in readers with and without dyslexia. Issue 2 (February 2023) - Egan, Ciara; Siyanova-Chanturia, Anna; Warren, Paul; Jones, Manon W
For skilled readers, idiomatic language confers faster access to overall meaning compared with non-idiomatic language, with a processing advantage for figurative over literal interpretation. However, currently very little research exists to elucidate whether atypical readers—such as those with developmental dyslexia—show such a processing advantage for figurative interpretations of idioms, or whether their reading impairment implicates subtle differences in semantic access. We wanted to know whether an initial figurative interpretation of similes, for both typical and dyslexic readers, is dependent on familiarity. Here, we tracked typical and dyslexic readers' eye movements as they read sentences containing similes (e.g., as cold as ice ), orthogonally manipulated for novelty (e.g., familiar: as cold as ice, novel: as cold as snow ) and figurativeness (e.g., literal: as cold as ice [low temperature], figurative: as cold as ice [emotionally distant]), with figurativeness being defined by the sentence context. Both participant groups exhibited a processing advantage for familiar and figurative similes over novel and literal similes. However, compared with typical readers, participants with dyslexia had greater difficulty processing similes both when they were unfamiliar and when the context biased the simile meaning towards a literal rather than a figurative interpretation. Our findings suggest a semantic processing anomaly in dyslexic readers, which we discuss in light of recent literature on sentence-level semantic processing.